A General Route to Hollow Mesoporous Rare‐Earth Silicate Nanospheres as a Catalyst Support. Issue 8 (21st January 2014) - Jin, Renxi; Yang, Yang; Zou, Yongcun; Liu, Xianchun; Xing, Yan
Abstract Hollow mesoporous structures have recently aroused intense research interest owing to their unique structural features. Herein, an effective and precisely controlled synthesis of hollow rare‐earth silicate spheres with mesoporous shells is reported for the first time, produced by a simple hydrothermal method, using silica spheres as the silica precursors. The as‐prepared hollow rare‐earth silicate spheres have large specific surface area, high pore volume, and controllable structure parameters. The results demonstrate that the selection of the chelating reagent plays critical roles in forming the hollow mesoporous structures. In addition, a simple and low‐energy‐consuming approach to synthesize highly stable and dispersive gold nanoparticle–yttrium silicate (AuNPs/YSiO) hollow nanocomposites has also been developed. The reduction of 4‐nitrophenol with AuNPs/YSiO hollow nanocomposites as the catalyst has clearly demonstrated that the hollow rare‐earth silicate spheres are good carriers for Au nanoparticles. This strategy can be extended as a general approach to prepare multifunctional yolk–shell structures with diverse compositions and morphologies simply by replacing silica spheres with silica‐coated nanocomposites.